Nilai Moderasi Islam dalam Proses Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama Islam Al-Azhar Kota Kediri - Arifin, Zaenal; Aziz, Bakhril (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This article discusses how the process and method of learning Islamic Religious Education in instilling the value of Islamic moderation in the Al-Azhar Kediri Islamic Middle School. The value of Islamic moderation is very important for someone to live in a pluralistic country like Indonesia. Therefore, it is really needed the right process and method in instilling these values. This study uses a qualitative method. While the type of research approach used is the phenomenological approach. While the data collection techniques used are observation, interview and documentation. While the data analysis technique uses the Milles and Huberman models. The results showed that the learning process of Islamic Religious Education in instilling the value of Islamic moderation in the Al-Azhar Kediri Islamic Middle School using learning materials based on the Ahlussunah Waljama'ah Annahdliyah Islamic approach using the exemplary approach and advice